Analisis Keuangan Pemerintah Daerah Kota Padang Tahun 2014-2018 untuk Mengukur Kinerja Keuangan Daerah - Arnaldi Arnaldi; Irdha Yusra (JURNAL PUNDI, 2020)
This study aims to assess the financial performance of Padang City Government using Financial Ratio Analysis of Regional Budget for the Fiscal Year 2014 – 2018. Type of research is descriptive qualitative with case study approach. The processed data is the budget  Report of Padang City Government for Fiscal Year 2014 – 2018 were obtained from the internet publication on the official website of the financial management board and regional property of Padang City. The analysis used to analyze the regional financial performance is financial analysis by calculating the ratio of independence, Degree of Fiscal Decentralization,  Ratio of Efficiency and Ratio of Expenditure Congruence. While the analysis used to analyze the Ability of Regional Finance is to calculate the Share and Growth, Map of Regional Finance Capability and,  Based on the calculation and analysis of the Regional Financial Performance can be concluded that the pattern of the region’s autonomy level relationships in Padang City is instructive criteria. Degree of Fiscal Decentralization is still lacking, but the Ratio of Efficiency is also not efficient. The ratio of Expenditure Congruence shows the balance between expenditures is not balanced. Based on the calculation and analysis of the Regional Financial Capability can be concluded, that the condition of the financial ability of Padang City is still not ideal. Share and Growth calculation results, the position of Padang City in quadrant III